A novel direct matching network synthesis technique and its application to broadband class‐J power amplifier. Issue 11 (8th August 2020) - Zeng, Maoning; Chen, Shichang; Wang, Weiwei; Cai, Jialin; Cao, Wenhui; Zhou, Xin Yu; Chan, Wing Shing; Wang, Gaofeng
Abstract: A novel direct matching network (MN) synthesis method improving the conventional simplified real frequency technique (SRFT) is presented in this article. By straightforwardly optimize the characteristic impedance (physical width) and electrical length (physical length) of each distributed element in a preselected configuration, the proposed method has one more degree of design freedom by comparison with the SRFT, and therefore increases design flexibility and matching effects. To demonstrate its effectiveness, a broadband class‐J power amplifier (PA) is devised for which both the input and output MNs are realized using the proposed method. The simultaneous manipulation of fundamental and second harmonic impedances is successfully realized by defining a novel target function that indicates the degree of proximity for the realized impedances to the optimal transistor impedances. Comprehensive equations and complete design procedures of the new technique are given. The measured class‐J PA implemented for verification achieves an output power of 39.2 to 42.3 dBm and power‐added efficiency of 61.8% to 71.6% over the frequency range of 2.5 to 3.8 GHz using a 10‐W GaN HEMT. A 20‐MHz LTE‐A signal is employed to validate the linearization capability of this class‐J PA. An adjacent channel leakage ratio level around −43.8 dBc is achieved after utilizing digital predistortion technique.